Дескриптивний аналіз лінгвокультурного типажу з соціальною домінантою "чиновник" у художньому дискурсі - Сукаленко, Т. (Філологічний дискурс, 2020)
У статті проаналізовано поняттєві та образно-перцептивні
характеристики канцелярських, судових і поштових чиновників,
представлених в українській літературі ХІХ ст. Класифіковано чиновництво за такими групами: канцелярські чиновники
(канцелярист, секретар, реєстратор, столоначальник, письмоводитель, секретар, писар); судові чиновники – суддя, підсудок,
писар в земському суді, секретар суду; поштові чиновники. Встановлено, що в описі канцелярських чиновників релевантними є
зовнішні, внутрішні моральні, мовні та релігійні характеристики. Акцентовано увагу на внутрішніх моральних характеристиках
судових чиновників ХІХ ст., провідними рисами яких були схильність до доносів і хабарництво. Закцентовано увагу на описі поштових
чиновників, представлених у творах підавстрійських письменників, які зображені як активні учасники виборів, політичного життя. The article deals with the analysis of the conceptual and figurative-perceptional
characteristics of stationery, court and postal officials presented in the Ukrainian
literature of the nineteenth century. As the material for the description of the type we used different fictional
discourse of the XIX century (prose, dramatic, poetical, etc.) of Ukraine under
Russian and Avstrian governing. We emphasised in the work that the linguocultural type is one of the special
kinds of linguocultural concepts, the most important characteristics of which are
motivated by the typicality of certain personality, its significance for the certain
linguoculture. Due to the established approaches to the description of the concepts in
the structure of linguocultural types, their conceptual, figurative-perceptive
components are consistently revealed. The officials are classified in the following groups: office officials (stationery,
secretary, registrator, stolonachalnyk, clerck, scribe); court officials - judge, judge
assistant, scribe in zemskyi court, secretary of the court; postal officials.
It has been found out that there are actual external, internal moral, lingual and
religious characteristics in the description of officers. The attention is focused on the
internal moral characteristics of court officials of the nineteenth century, the leading
features of which there were the tendency to denunciations and bribery. It is emphasised that in the fictional discourse of the nineteenth century the lingual characteristic of the type of « official» is important. Two types of officials are
represented here: the first - the lowest – Ukrainian language-speaking; the second
one - who lost the relationship with the native language and uses Russian.
The attention is focused on the description of postal officials, represented in the works of the writers in Ukraine under the Austrian governing, which are depicted as active participants in the elections, political life.